First record of Bugula neritina (Bryozoa: Bugulidae), in the mediolittoral zone of Ibn ‎Hani Lattakia, eastern Mediterranean sea (Syria)‎ - Arabia, Izzat W.; Ammar, Izdihar A.; Ali, Abdel-latif Sh. (Mesopotamian Journal of Marine Sciences, 2023)
The species Bugula neritina (Linnaeus, 1758) of the Bugulidae family was observed on the artificial reefs at a depth of 15 meters, (from February to May2021) in the mediolittoral waters of Ibn Hani site (north Lattakia City, Syria). The morphological and characteristics have been used to confirm the new Bryozoa. It is the first record of this species in the Syrian marine waters. B. neritina colonies abundance are 3 colonies in 1200cm2, and they were found with coralligenous macroalgae, Codium sp (green algae), Polysiphonia sp. (red algae), Balanus and Tunicates, attached to hard substrate (artificial reefs), in salinity 39‰).